2020
DOI: 10.1371/journal.pone.0238639
|View full text |Cite
|
Sign up to set email alerts
|

The burden of HIV infection among men who purchase sex in low- and middle-income countries – a systematic review and meta-analysis

Abstract: Background Since the start of the HIV epidemic, transactional sexual relationships have been considered to present a high risk of HIV transmission to both the client and the person offering the sexual service. However, prevention research and programs have focused predominantly on sex workers rather than on their clients, who are generally men. To support effective and targeted interventions, we undertook a systematic review and meta-analysis of the evidence of the prevalence of HIV infection among men who pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Age, education level, residence, and lack of HIV/AIDS knowledge were some factors associated with willingness to use PrEP reported in previous studies (15,21). In addition, stigma, fear of side effects, and poor user awareness were identi ed as possible factors of willingness to use PrEP (15,22,23); and fear of stigma, cost, and drug-drug interaction were also reported (12,18,24,25).…”
Section: Introductionmentioning
confidence: 84%
“…Age, education level, residence, and lack of HIV/AIDS knowledge were some factors associated with willingness to use PrEP reported in previous studies (15,21). In addition, stigma, fear of side effects, and poor user awareness were identi ed as possible factors of willingness to use PrEP (15,22,23); and fear of stigma, cost, and drug-drug interaction were also reported (12,18,24,25).…”
Section: Introductionmentioning
confidence: 84%
“…This meta-analysis also estimated that only 67.5% of men surveyed between 2010 and 2020 reported using a condom during their last paid sex encounter. A second meta-analysis of 44 studies in low-income and middle-income countries conducted between 1989 and 2019 also found an elevated risk of HIV among men who purchased sex (5% pooled HIV prevalence; n=21 studies), and in studies conducted between 2011 and 2019 (2.85%), compared with men who did not purchase sex 1. Thus, an effective response to the elevated HIV vulnerability experienced by MC is essential to controlling the HIV epidemic, particularly in East and Southern Africa, where MC and other sexual partners of key populations, including FSW, accounted for 15% of new infections among those aged 15–49 years in 2019 4.…”
Section: Introductionmentioning
confidence: 95%
“…A second meta-analysis of 44 studies in low-income and middle-income countries conducted between 1989 and 2019 also found an elevated risk of HIV among men who purchased sex (5% pooled HIV prevalence; n=21 studies), and in studies conducted between 2011 and 2019 (2.85%), compared with men who did not purchase sex. 1 Thus, an effective response to the elevated HIV vulnerability experienced by MC is essential to controlling the HIV epidemic, particularly in East and Southern Africa, where MC and other sexual partners of key populations, including FSW, accounted for 15% of new infections among those aged 15–49 years in 2019. 4 However, data on factors associated with risk of HIV acquisition as well as studies of HIV prevention interventions among this population are limited, likely due to stigma, difficulty in identifying them and varying legality of commercial sex across countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, high-risk behaviours, such as unprotected sex with multiple casual female partners or female sex workers (FSWs) and injecting drug use (IDU) practices, have been reported as proximal or direct factors that facilitate HIV transmission among men. [5][6][7][8][9][10] Poor general knowledge about HIV and condoms for prevention is another contributing factor for HIV transmission among men as it leads to men being unaware of the possibility of contracting HIV through such high-risk behaviours they engage in. [11][12][13] Men's negative attitudes towards condom use, past negative experiences of condom use practices in previous sexual encounters, 12,14,15 substance abuse and alcohol consumption prior to sex, [15][16][17] and intention to avoid sex partner's suspicion about their sexual relations with other women, 16,18 are all supporting reasons for men's engagement in unprotected sex.…”
Section: Introductionmentioning
confidence: 99%